SUNNAH SEBAGAI SUMBER IPTEK DAN PERADABAN (Studi atas Pemikiran Yusuf Al-Qardhawi) - Mosiba, Risna (Inspiratif Pendidikan, 2017)
The topic of this paper is sunnah as a source of science and civilization. This topic is a new issue for Muslim intellectual treasures. Although the study has roots in turbans (inheritance) of Islamic knowledge, however the issue is so deep that it needs to be explored and disclosed in general. This issue is one of the topics that concerns the intellectuals of the IIIT institute (International Institute of Islamic Thought) in Washington. They then asked the intellectual of Islam to conduct the study. The discussion of Yusuf al-Qardhawi about sunnah as a source of science, technology and civilization, can be seen in his monumental masterpiece entitled al-Sunnah; Mashdaran lil Ma'rifat al-Hadharah. The thickness of this book reaches 311 pages and the content of the discussion consists of five main components. First, the introduction is an overview of the book's description. Second, tasrif Aspect (Yuridis) in the Sunnah. Third, sunnah as a Source of knowledge. Fourth, sunnah as a source of civilization. Fifth, the closing part.